HUBUNGAN TINGKAT AKTIVITAS FISIK DAN EMOTIONAL EATING DENGAN OBESITAS PADA REMAJA: STUDI CROSS-SECTIONAL di SMA SURAKARTA - Faradisa, Elok; Kusumawati, Mira Wahyu; Rosida, Nikma Alfi; Rahmad, Muhamad Nur (Prodi Keperawatan Tegal Program Diploma III Poltekkes Kemenkes Semarang, 2025)
Obesity in adolescents is a rising health issue that can lead to metabolic and psychological problems. This study aims to identify the relationship between physical activity and emotional eating with the occurrence of obesity in adolescents. A quantitative non-experimental study with a cross-sectional design was conducted. The sample consisted of 72 students from grades X and XI with a BMI ≥ 23, selected using random sampling. Data were collected using the International Physical Activity Questionnaire (IPAQ) and the Dutch Eating Behavior Questionnaire, along with anthropometric measurements to assess BMI. Data analysis was performed using Spearman’s rho test with SPSS. The majority of adolescents with low physical activity levels were classified as Obese 2 (BMI ≥ 30), and high emotional eating was also significantly associated with obesity. Both variables showed a significant correlation with p-values < 0.05. Low physical activity and high emotional eating are major risk factors for obesity in adolescents. It is recommended that schools and government authorities enhance physical activity programs and emotional management education to prevent obesity. Support from family and the environment is also crucial to reinforce healthy lifestyles among adolescents.